Efficacy of Brodalumab and Guselkumab in Patients with Moderate-to-Severe Plaque Psoriasis Who are Inadequate Responders to Ustekinumab: A Matching Adjusted Indirect Comparison - Hampton P (Dove Medical Press, 2021)
Philip Hampton,1 Emma Borg,2 Jes Birger Hansen,2 Matthias Augustin3 1Department of Dermatology, The Newcastle Upon Tyne Hospitals NHS Foundation Trust, Newcastle, UK; 2LEO Pharma A/S, Ballerup, Denmark; 3Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf (UKE), Hamburg, GermanyCorrespondence: Philip HamptonDepartment of Dermatology, The Newcastle Upon Tyne Hospitals NHS Foundation Trust, Newcastle, NE7 7DN, UKEmail philip.hampton@nhs.netPurpose: Both brodalumab and guselkumab improve skin clearance in patients with moderate-to-severe plaque psoriasis after inadequate response to ustekinumab. In the absence of a direct head-to-head comparison, the relative efficacy of brodalumab and guselkumab in non-responders to ustekinumab were compared using a matching-adjusted indirect comparison (MAIC).Patients and Methods: Individual patient data for brodalumab (n = 121) were pooled from the AMAGINE-2 and -3 trials and adjusted using a propensity score reweighting method, so that baseline and week 16 characteristics matched the aggregate published data of patients with an inadequate response to ustekinumab who switched to guselkumab (n = 135) in the NAVIGATE trial.Results: After inadequate response to ustekinumab, brodalumab resulted in significantly higher psoriasis area and severity index (PASI) 90 rates versus guselkumab at post-treatment switch week 12 (62.7% vs 48.1%, relative difference 14.6% [95% confidence interval [CI] 5.3– 23.9], p = 0.002 [number needed to treat [NNT] = 6.8]) and week 36 (63.7% vs 51.1%; relative difference 12.6% [95% CI 4.1– 21.0]; p = 0.004 [NNT = 7.9]) and PASI 100 rate at week 36 (40.3% vs 20.0%; relative difference 20.3% [95% CI 11.8– 28.7]; p < 0.001 [NNT = 4.9]).Conclusion: In this MAIC, brodalumab was associated with greater improvements than guselkumab in inadequate responders to ustekinumab. Switching to brodalumab in such patients may be a more effective strategy than switching to guselkumab.Keywords: brodalumab, guselkumab, psoriasis